Mechanical and Thermal Performance of Fly Ash–Clay Modular Walls in Micro House Net Zero Energy Implementation - Permana, Asep Yudi (Journal of Development and Integrated Engineering, 2025)
The construction sector faces increasing pressure to reduce energy consumption and embodied carbon, encouraging the development of sustainable building components based on industrial waste. This study evaluates the mechanical and thermal performance of modular wall systems developed from fly ash–clay composites as part of a 2025 research downstreaming program for Micro House Net Zero Energy (NZE) implementation. An applied experimental and descriptive–evaluative method was employed. Mechanical performance was assessed through compressive strength testing, showing values ranging from 7.8–9.5 MPa, which meet the requirements for low-rise residential buildings. Thermal performance evaluation indicates that the modular wall system achieves a thermal conductivity of approximately 0.45–0.52 W/mK, demonstrating improved heat resistance compared to conventional masonry walls. The modular configuration also reduced construction time by approximately 25–30% compared to conventional brickwork. These results confirm that fly ash–clay modular walls provide adequate structural capacity, enhanced thermal performance, and construction efficiency, supporting their application in Micro House NZE systems and strengthening the industrial readiness of waste-based construction materialsKeyword: Modular wall, fly ash–clay, mechanical performance, thermal performance, net zero energy housingy